2010
DOI: 10.3354/esr00249
|View full text |Cite
|
Sign up to set email alerts
|

Potential for rat predation to cause decline of the globally threatened Henderson petrel Pterodroma atrata: evidence from the field, stable isotopes and population modelling

Abstract: Past studies have indicated that Pacific rats Rattus exulans are significant predators of the chicks of surface-breeding seabirds, namely gadfly petrels Pterodroma spp., on Henderson Island, central South Pacific. Further fieldwork in 2003 confirmed the heavy predation of chicks of Murphy's petrel P. ultima by rats. By extension, heavy predation is also likely each year on the endangered Henderson petrel P. atrata, for which Henderson Island is the only confirmed breeding site. To assess how important petrels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Available estimated adult survival rate in other Pterodroma is 0.93 (Simons ; Brooke et al . ), and age of sexual maturity in other Pterodroma is approximately 6 years of age (Simons ; Warham ). Thus, using values of 0.93 and 6 for p and A, respectively, equation (1) gives a generation time T of approximately 20 years.…”
Section: Methodsmentioning
confidence: 99%
“…Available estimated adult survival rate in other Pterodroma is 0.93 (Simons ; Brooke et al . ), and age of sexual maturity in other Pterodroma is approximately 6 years of age (Simons ; Warham ). Thus, using values of 0.93 and 6 for p and A, respectively, equation (1) gives a generation time T of approximately 20 years.…”
Section: Methodsmentioning
confidence: 99%
“…On Henderson Island, inferences about historical seabird population sizes have been made based on backward extrapolation of current rates of decline and population sizes to the time at which rats colonized the island; they suggest that millions of pairs of gadfly petrels Pterodroma spp. may have been lost (de Brooke et al. 2010).…”
Section: Historical Impacts Of Invasive Mammalian Predatorsmentioning
confidence: 99%
“…In most cases, data are inadequate to determine whether this is the case, but several lines of evidence suggest that some populations and communities may still be in decline. de Brooke et al. (2010) have shown that where breeding success of long‐lived petrel species is chronically reduced by invasive predators, population declines can continue over many centuries before extirpation finally occurs.…”
Section: Current Impactsmentioning
confidence: 99%
“…Adopting a generalist diet is one of the key adaptations that has contributed to the success of mice and rats, and that has allowed them to inhabit almost every ecosystem . Hunting even other vertebrates such as birds for prey, rats also endanger seabird colonies on islands, and as invasive species in New Zealand, both brown rats, Rattus norvegicus , and black rats, R. rattus , greatly harm the indigenous fauna . When humans realized the many adverse effects associated with the presence of rats and mice, they designed tactics to trap them, in turn exerting selective pressure on mice and rats to evolve counteradaptations.…”
Section: Introductionmentioning
confidence: 99%